Disparitas Implementasi Kebijakan Pengendalian Daya Rusak Air: Studi Kritis Efektivitas Kinerja Bbws Citarum Wilayah Bandung Selatan - Zulfi Ashari; Muhammad Faiz Zakwan (Yayasan Al-Afif, 2025)
This article analyzes the disparity between the regulation of water destructive power control and its implementation in the South Bandung region, focusing on the performance of the Citarum River Basin Agency (BBWS Citarum). Employing a juridical-empirical approach, the research finds that although BBWS has attributive authority based on Law No. 17 of 2019 on Water Resources and Ministerial Regulation PUPR No. 16 of 2020, its effectiveness is hindered by structural, substantive, and legal culture factors according to Lawrence M. Friedman's Legal System Theory. Empirical data indicates recurrent flooding in Dayeuhkolot, Baleendah, and Bojongsoang in 2025 despite operational infrastructure projects such as the Nanjung Tunnel and retention ponds. The conclusion recommends cross-sectoral regulatory synchronization and a preventive approach to address this gap, aiming for more sustainable water resource management